DIARRHEA POISONING AND COURSE IN PATIENTS, TREATMENT METHODS (World Bulletin of Public Health, 2023)
The main causes of acute diarrhea are infection and malnutrition. Acute diarrhea is also associated with the consumption of food (seafood) stored in unhygienic conditions or contaminated during irrigation.
Keywords: conditions; contaminated; infection; diarrhea